REVITALIZATION OF CULTURAL IDENTITY USING SIGNS-SYMBOLS - Moțăianu, Cornelia (Design/Arts/Culture, 2023)
The preoccupation of many scholars to save the Romanian cultural heritage has been a constant topic. Architects, archaeologists, historians, art historians, and designers compete to preserve the image of the past and the spiritual richness of tradition with the help of various modern technological tools. Visual design is increasingly used in cultural projects. This project of visual design, of revitalizing the cultural identity of a village, wants, not only to bring unknown information about the culture of a place, but is also an invitation to preserve the fascinating value of the identity of the traditional society, represented by the crafts and folk customs that have survived until today. By synthesizing the essence of traditional patterns inherited from the past, an intuitive system of visual identity represented by signs has resulted, which introduced the interested public to the cultural and historical atmosphere of the researched region. These signs become symbolic representations of the village’s tangible and intangible heritage. A sign-symbol was created for each element of the local tradition, which will be part of the infographic that will concisely present certain cultural processes.